Simulation, Experimental and Analitical Study of Deflection at End Curved Beam Affected by Single Concentrated Load - Putra Negara, Dewa Ngakan Ketut; Sri Komaladewi, Anak Agung Istri Agung (Jurnal Energi Dan Manufaktur; Vol 3, No.1 April 2009)
Deflection has an important role in order to design structure or machine component, beside consideration of stresscalculation. This is due to although stress is still smaller then stress allowed by material strength, but probably happen thatdeflection exceeds limit allowed. That condition affects serious hazard on machine elements or structure due to it can affectof component deviate from its main function. One of element which is often experience of deflection is beam. Beams playsignificant roles in many engineering applications, including buildings, bridges, automobiles, and airplane structures. In thisresearch, material to be used was Steel ASTM 1060, with specimen in the form of curved beam. Physical condition of beamwas modeled use of BEAM3 2D. Variation of loads to be applied were W = 100, 150, 200, 250, 300, 350, 400, 450, 500, and550 gr in vertical direction. The result of simulation was verificated by analytical and experimental data. Evaluation wascarried out by statistical test (t-test). The result of simulation is categorized to be good if the result of simulation is samewith analytical and experimental data. The result of research shows that loading has a significant effect on the deflection.The higher load affect the higher of deflection Modeling use of BEAM3 2D gave good result of deflection. This is showedfrom t-test have done, where the result of simulation was same with analytical and experimental data. Other advantage ofsimulation was deflection result obtained was not limited only at the end of beam, but it can predict of deflection at eachnode or point desired
Keywords: Simulation, Deflection, Beam